PROTAGONIST’S FRIENDS’ BETRAYAL IN JAY ASHER’S NOVEL THIRTEEN REASONS WHY - Fairuz Aini Pane; Andang Suhendi (Universitas Islam Sumatera Utara, 2023)
This study discusses the protagonist's friends' betrayal in the novel Thirteen Reasons Why by Jay Asher. This study aims to reveal the types of betrayal of the protagonist's friends and to describe the impacts of the protagonist's friends' betrayal. Larson's theory is used in this research. It takes about the types of betrayal. Then, Reis’ and Spencer's theory are taken to deal with the impacts of betrayal. This study uses a descriptive qualitative method to reveal the data. The data was originally taken from the novel. It is found that five data are to reveal the type of betrayal and twelve data to describe the impacts of betrayal. The results of this study indicate that there are two types of betrayal received by Hannah, i.e., intimate partner betrayal and interpersonal betrayal. It is also found that the impacts Hannah received as a result of the betrayal of her friends are loss of trust, loss of relationship/friendship, loss of sense of security, and loss of self-esteem. All data in this study prove that the protagonist’s friends in the novel betray her.